Deciphering the role of forkhead transcription factors in cancer therapy - Yang, Jer-Yen; Hung, Mien-Chie (Current drug targets, 2011)
Forkhead O transcription factors (FOXO) are critical for the regulation of cell cycle arrest, cell death, and DNA damage repair. Inactivation of FOXO proteins may be associated with tumorigenesis, including breast cancer, prostate cancer, glioblastoma, rhabdomyosarcoma, and leukemia. Accumulated evidence shows that activation of oncogenic pathways such as phosphoinositide-3-kinase/AKT/IKK or RAS/mitogen-activated protein kinase suppresses FOXO transcriptional activity through the phosphorylation of FOXOs at different sites that ultimately leads to nuclear exclusion and degradation of FOXOs. In addition, posttranslational modifications of FOXOs such as acetylation, methylation and ubiquitination also contribute to modulating FOXO3a functions. Several anti-cancer drugs like paclitaxel, imatinib, and doxorubicin activate FOXO3a by counteracting those oncogenic pathways which restrain FOXOs functions. In this review, we will illustrate the regulation of FOXOs and reveal potential therapeutics that target FOXOs for cancer treatment.